A CONCEPTUAL MODEL OF THE EXTERNAL COSTS OF TRUCK OVERLOADING ON ROAD DAMAGE, EMISSIONS, AND TRAFFIC CONGESTION: A SYSTEMATIC LITERATURE REVIEW - sitepu, aleksius; Soehodho, Sutanto; Kusuma, Andyka (Smart City, 2026)
Freight transport services cannot be separated from the infrastructure and facilities involved, each of which faces its own challenges in delivering optimal performance in the logistics sector. A common challenge in Indonesia’s road sector is the presence of overloaded freight vehicles, which has become a national issue. This phenomenon has a negative impact not only on road infrastructure but also on the environment and traffic. This study aims to develop a conceptual model of the external costs caused by truck overloading practices in terms of road infrastructure damage, increased exhaust emissions, and traffic congestion through a systematic literature review. This phenomenon is a global issue that has significant economic, environmental, and social impacts. The research method employed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach by analyzing 87 scientific articles from the Scopus, Web of Science, and Google Scholar databases covering the period 2015–2024. The results of the study can be categorized into three main components: (1) to systematically review the isolated external costs associated with pavement damage, emissions, and congestion, (2) to quantify the interconnected relationships and multiplier effects between these variables, and (3) to propose an integrated conceptual causal-chain model that delineates the compounded external costs of ODOL operations. The conceptual model developed integrates these three cost components while taking into account factors such as axle load, road pavement conditions, traffic characteristics, and applicable regulations. The findings of this study provide a comprehensive framework for policymakers to calculate the total costs of overloading externalities and to design appropriate economic instruments for internalizing these external costs.